Prospektif Identifikasi Kejadian Prescribing Error di Instalasi Rawat Jalan (IRJ) RSUP Fatmawati Periode November 2025 - Yasmin Masyhura (RSUP Fatmawati, 2025)
Prescribing errors often serve as an initial gateway to broader medication errors in hospital patient care. These errors must be minimized, particularly through digitalization efforts such as e-prescribing. This study aimed to identify prescribing errors in outpatient prescription services at Fatmawati Central General Hospital following the implementation of a hospital-wide e-prescribing system. A prospective direct observation method was applied to all prescriptions received at the Outpatient Pharmacy Depot, supported by clarification with the responsible pharmacists to ensure contextual accuracy and data validity. In November 2025, a total of 10,842 outpatient prescriptions were recorded. Several prescribing errors were still found during the observation period, including input errors such as mistyping and incorrect drug selection. High-risk drug interactions, especially among patients using warfarin, required closer monitoring. Patient education on the use of medications requiring special devices was also not consistently delivered. Meanwhile, prescriptions for narcotic and psychotropic medications complied with indication requirements and prescribing limits set by the National Formulary. These findings indicate that e-prescribing effectively reduces the frequency of errors compared with manual prescriptions. The results also underscore the need for enhanced prescription verification, improved patient counseling, and further optimization of the e-prescribing system.